Ennis Franciscan Friary, tomb niche, north nave wall, pinnacle - O'Donovan, Danielle (My University, 2008)
Pinnacle flanking tomb niche. Similar tomb nices occur at Quin, Adare Franciscan, Adare Augustinian, Askeaton, Lislaughtin, Abbeydorney and Kilconnell.
Keywords: Architecture, Gothic -- Ireland; Ennis (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; pinnacles